HYPOTHESES TESTING ON THE VALIDITY OF EFFECTIVE COMMUNICATION AND COMMON MOTIF OF SELAYAH KERINGKAM - Qistina Donna, Lee Abdullah; Norsyahbany, Mansor (UNIMAS Publisher, 2021)
This paper is to deliberate the subjects of the effective communication channel in delivering common motifs in Selayah Keringkamby assessing the local and International tourists’ preference. It is to evaluate the hypotheses Testing On validity of Effective Communication and Common Motif of Selayah KeringkamTowards the communication channel. The finding of this paper is to enhance the implications on developing a significant way to disseminate Selayah Keringkam as a heritage product in Sarawak. This paper will expose a substantial relationship between the independent variables (Common Motif of Selayah Keringkam), the dependent variables (Channels of Communication) and the mediator (Supplement of Effective Communication) as a new framework to the body of knowledge. This research involved 384 respondents with 5 relevant authorities related to answering research questions. The data collected from the fieldwork were analysed using SPSS version 24. The measures used in this article are methodically deliberated using factor analysis and correlation analysis. Lastly, the results of the regression analyses testing on hypotheses and summary of hypotheses assessments are presented.